STRESS IN COMMUNICATION IN FAMILIES TAKING CARE ABOUT PERSONS AFTER COMA AWAKENING - (:unkn) unknown (SIAULIAI UNIV & OPEN INT UNIV HUMAN DEV UKRAINE, 2016)
The article presents the results of the pilot research, which reveals the communication in a family taking care of their adult children after awakening from coma. The research is sponsored by Erasmus+ project Links United for Coma Awakenings through Sport No. 557075-EPP-1-2014-1-IT-SPO-SCP. Analysing the results of family communication and coping with stress qualitative research was applied. The results show that family members taking care about their adult children awakening after coma experience a different level of stress. Communication peculiarities reflect the lack of communication skills. The ways to cope with stress in the communication process are individual and based on self-realization and meeting of emotional needs of the family.
Keywords: Parents; stress; communication skills; coma awakenings; TRAUMATIC BRAIN-INJURY